Does private aid follow the flag? An empirical analysis of humanitarian assistance - Andreas Fuchs; Hannes Öhler (Kiel Institute for the World Economy (IfW), 2019)
Little is known about foreign aid provided by private donors. This paper contributes to closing this research gap by comparing the allocation of private humanitarian aid to that of official humanitarian aid awarded to 140 recipient countries over the 2000-2016 period. We construct a new database that offers information on the country in which the headquarters of private donors are located to test whether private donors follow the aid allocation pattern of their home country. Our empirical results confirm that private aid "follows the flag." This finding is robust against the inclusion of various fixed effects, estimating instrumental variables models, and disaggregating private aid into corporate aid and NGO aid. Donor country-specific estimations reveal that private aid from China, Sweden, the United Kingdom, and the United States "follow the flag".
Keywords: H84; F35; F59; 330; foreign aid; humanitarian assistance; disaster relief; aid allocation; private donors; non-governmental organizations; corporations; private foundations